Physical and chemical properties and antioxidant characteristics of gac aril juice fermented with Aspergillus niger - Mungkunkoth, Kessara; Deeseenthum, Sirirat; Luang-In, Viitra (Food Agricultural Sciences and Technology, 2025)
Gac (Momordica cochinchinensis (Lour.) Spreng) is a medicinal herb that contains carotenoid substances, phenolic compounds, and ﬂavonoids, and is well-known for reducing the risks of coronary heart disease and prostate cancer. This study investigated the carotenoid and antioxidant properties of Gac aril juice fermented for a 48-hour fermentation process with 2% (v/v) Aspergillus niger. The fermented juice exhibited an orange hue with L*, a*, and b* values of 51.47±4.50, 28.37±1.16, and 43.19±0.97, respectively. Total dissolved solids (TDS) decreased to 8.20±0.69 °Brix, and pH also decreased during fermentation. High-performance liquid chromatography (HPLC) revealed higher lycopene (8349.48 µg/100 mL) and β-carotene (57.09±0.64 µg/100 mL) contents than the control. Antioxidant activity, assessed using 2,2′-diphenyl-1-picrylhydrazyl (DPPH) and ferric ion-reducing antioxidant power (FRAP) assays, increased with fermentation time. At 48 hours, DPPH activity reached 1.76±0.01 µg of TE/mL, and FRAP activity reached 108.92±0.78 µg Fe (II)/mL. Total phenolic content (TPC) and total ﬂavonoid content (TFC) were 267.30±1.53 µg GAE/mL and 742.10±2.65 µg RE/mL, respectively. Fermented Gac aril juice with A. niger contained CO₂ and carbamic acid, which were not found in the non-fermented juice. Our findings created value-added products, such as health-promoting beverages and cosmetic ingredients.